2013
DOI: 10.1097/dcr.0b013e318286c518
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Stratification of TNM Stage III Rectal Cancer Based on the Presence/Absence of Extracapsular Invasion of the Metastatic Lymph Nodes

Abstract: Detailed stratification of pN3 cases based on the presence/absence of extracapsular invasion in metastatic lymph nodes has the potential to contribute significantly to more available prediction of the prognosis of patients with stage III colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…However, the prognostic influence of ECNI in colon cancer has not widely been accepted. Recently, two studies have demonstrated the prognostic importance of ECNI in colon and rectum cancer patients . Consistent with these findings, ECNI was found to be the strongest predictor for early recurrence and relapse risk in our study.…”
Section: Discussionsupporting
confidence: 92%
“…However, the prognostic influence of ECNI in colon cancer has not widely been accepted. Recently, two studies have demonstrated the prognostic importance of ECNI in colon and rectum cancer patients . Consistent with these findings, ECNI was found to be the strongest predictor for early recurrence and relapse risk in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Altogether, 210 nonduplicated articles were identified through the literature search. After excluding 189 articles based on title/ abstract review, 21 articles were retrieved for full-text review and following the application of the inclusion criteria, 13 unique articles were eligible for the meta-analysis [18][19][20][21][22][23][24][25][26][27][28][29][30] (supplementary Figure S4, available at Annals of Oncology online).…”
Section: Results Search Resultsmentioning
confidence: 99%
“…In more recent years, several studies have reported the clinical significance of LPLN metastasis and have attempted to stratify patients with LPLN metastasis. 5 , 6 , 9 , 25 28 Ueno et al 27 demonstrated that the number of LPLN metastases had a significant association with prognosis: patients with two or more LPLN metastases demonstrated a poorer prognosis than those with only one LPLN metastasis. Akiyoshi et al 6 stratified patients with LPLN metastasis according to anatomic location, finding that patients with external LPLN metastasis showed a worse prognosis than those with internal LPLN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Akiyoshi et al 6 stratified patients with LPLN metastasis according to anatomic location, finding that patients with external LPLN metastasis showed a worse prognosis than those with internal LPLN metastasis. Komori et al 28 showed that extracapsular invasion in the LPLN area was an independent prognosis factor correlated with OS and RFS rates. However, to date, no studies have addressed the clinical significance of EX in the LPLN area.…”
Section: Discussionmentioning
confidence: 99%